Nature et domotique du langage : Une approche des interactions naturelles homme-machine en environnement pervasif - François Perea (Corela)
Nowadays, our technological environment is characterized by a total computer dissemination in the intelligent and connected objects. In this context of Ambient Intelligence (Zelkha et al., 1998) the domotic devices are deployed in so-called '' natural'' interactions with humans. For example Google Home is presented as: "a voice-activated speaker that works with the Google Assistant" (https://madeby.google.com/home /, accessed 04/10/2017). We can also discuss with the competition agents: Amazon Echo, Apple HomePod, etc. These devices lead us to question a new step of "the technological revolution of language" (Auroux, 1994) and its automation (Léon, 2015), which makes machines real talking subjects, enrolled in a "human-machine coupling" "(Sadin, 2013). In this context of affordances (Gibson, 1977), we observe the modalities of the H/M interaction, characterized in particular by a conversational simulation and a personalization of the technological devices. Our perspective is post-dualistic and non-logocentric, in line with the current of discourse analysis (in interaction): Text-Speech-Interaction (Paveau, 2012).